I have found another way of finding the terms of a fibonacci numbers.
Fn F ) - ( F ) ;where x+y=n and y=x-2.
(or) Fn th term of the sequence is equal to the difference of squares of two fibonacci numbers F and F
where x+y=n and y=x-2
sum of first n terms of a fibonacci sequence is,
Sn = ( F ) - 1
Your notation is not showing up probably.
There are ways to show the fibonacci numbers (eg. phi).
I can not make out anything of what you have written. You could latex it up
Your last one:
In mathematics, you don't understand things. You just get used to them.
I have the result, but I do not yet know how to get it.
All physicists, and a good many quite respectable mathematicians are contemptuous about proof.